Intimacy and visual communication in social media: Editorial - Thorhauge, Anne Mette; Demant, Jakob Johan; Strøm Krogager, Stinne Gunder (MedieKultur: Journal of media and communication research, 2020)
Sharing (intimate) photos has become an integral part of close relationships in the age of social media. Most young people use social media as a way to establish and main- tain strong social ties rather than as a way of connecting to public life. This pattern of use includes the sharing of photos and videos with intimate and sexual content, such as nudes, intimate situations, and other types of self-disclosure. Given that the primary public and academic interest has been related to situations where the process has gone wrong and people have been hurt, these photos and videos are often associated with risk, worries, and moral disdain. However, these cases are part of a broader range of social practices, which are for the most part unproblematic and mundane. The sharing of inti- mate photos should be acknowledged as part of a more general act of (mutual) self-dis- closure to establish trust as well as an non-patalogical exploration of sexuality and social identities. In both cases, the sharing of intimate photos becomes part of more general processes of intimacy and close relationships that we should be careful not to reject or problematize as a whole. Accordingly, in this themed issue we would like to move beyond the stories of problem youth and move instead towards a more empirically grounded and systematic analysis of the complex ways in which the sharing of intimate photos becomes part of everyday life practices, including friendship, courtship, trust, and intimacy.